Higher education institution leadership competency model development using the KSA approach - Andika, Aditya (Enrichment : Journal of Management, 2025)
Higher Education Institutions (HEIs) need competent leaders to survive and thrive in today’s challenging educational environment. In order to achieve this, HEIs have to develop leadership competency models that are aligned with their needs and context. A leadership competency model is essential in understanding how to develop Higher Education Institution leaders. This study proposes a list of HEIs leadership competencies and a HEI leadership competency model based on knowledge-skills-attitudes (KSA) approach. The proposed model can be used as a foundational framework that can be adapted and customized by HEIs to develop their own unique models